A novel application of Monascuspurpureus in semi‐soft cheese making. Issue 3 (22nd January 2021) - Jiao, Jingkai; Liu, Zhenmin; Zheng, Yuanrong; Liu, Jing
Abstract: Monascus spp. and its rice fermentation products have been used as food colorants and flavor enhancers, as well as for meat preservation and wine brewing in the Asia for centuries. A novel application of Monascus purpureus in semi‐soft cheese making was introduced in this paper. The changes in the dynamics of the microbiota during cheese ripening were investigated in this study using high through‐put methods. The most dominant bacterial genus was determined to be Lactococcus, and the dominant fungal genus was Monascus . Also, some other genera were detected in the red cheese samples, such as Leuconostoc . Samples of the Cheese were analyzed using dynamic oscillating rheology and the result indicated an elastic solid character rheological behavior. It was observed that the level of citrinin produced by Monascus and other fungal genera in the examined Cheese samples was lower than that produced in the red yeast rice. Furthermore, the mevinolin and γ‐ aminobutyric acid were also presence in Cheese samples. Therefore, the results of this study suggested that M. purpureus has positive effects on cheese making processes. Novelty impact statement: A Novel Application of Monascus in Semi‐Soft Cheese making has been introduced by our investigated team, which is referred to as Red Cheese. The processing of the Red Cheese has been researched and introduced in this paper. The nutrient content, texture, microbiota, and some other features were also tested in this paper.